Lindernia Micrantha D. Don (Linderniaceae): A red listed plant species new discoveryto Tamil Nadu, India - Velayudham, L.; Jeyaprakash, K.; Balachandran, Natesan; Rajantheran, Muniandy (Plant Archives, 2020)
Lindernia micrantha D. Don is a red listed (Least Concern) species, recorded first time from Sathuragiri hills, Madurai District, Southern Western Ghats of Tamil Nadu, India. This communication brings with detailed description, distribution, phenology and photographs of the species for easy identification. © 2020 Plant Archives. All rights reserved.